Pemetaan Moluska Komoditas Ekspor dan Impor Melalui Balai Besar KIPM Jakarta I - Moh Muhaemin; Nabila Nabila; Henky Mayaguezz; Muhammad Gufron Purnama; Ishaaq Saputra (Journal of Marine Research, 2024)
Indonesia has high biodiversity and it has the opportunity to expand as fisheries business in the international commodity market. The research aims to analyze the diversity of mollusk species, map the distribution, and analyze the sustainability of these commodities in the Indonesian export and import markets. The research conducted at the Jakarta I Fish Quarantine Center for Quality Control and Safety of Fishery Products (BBKIPM) on January to February 2023. The data used comes from data available at BBKIPM Jakarta 1 on 2021 to 2022 periods. The method used is descriptive quantitative analysis. The results showed that mollusk commodities traded in exports were more diverse than imported mollusks. The most commodity classes are pelecypod (35 species), gastropods (12 species) and cephalopods (12 species). The total number of exported mollusk commodities (4,823,969.879 kg) is higher than imports (7,281.04 kg) on 2021 to 2022 periods. Mollusk exports from Indonesia spread to 44 countries on 2021 to 2022 periods. Meanwhile, mollusk imports to Indonesia only came from 2 countries (2021) and either from 1 country (2022).